Bob's toolbox mix-up - Thorpe, Kiki.; Mendenhall, Cheryl (New York : Simon Spotlight, 2002)
Bob needs to find his lost hammer in order to finish Wendy's house.
Cover title.
Board pages.
Lift-the-flap pages.
"Based upon the television series Bob the builder"--Cover p. [4].
Keywords: Bob the Builder (Fictitious character) -- Fiction; Construction workers -- Fiction; Construction equipment -- Fiction; Toy and movable books